CRYSTAL STRUCTURE OF A SYNTHETIC ALUMINOAN TANTALIAN TITANITE: A RECONNAISSANCE STUDY - Liferovich R.P.; Mitchell R.H. (My University, 2006)
A synthetic analogue, Ca(Ti 0.6Al 0.2Ta 0.16 Nb 0.04 )OSiO 4, of an aluminoan tantalian titanite previously described from Craveggia pegmatite (Piemonte, Italy) has been prepared by a ceramic synthesis technique and its crystal structure determined by Rietveld analysis of the powder X-ray diffraction pattern. The synthetic Al-Ta-Nb-rich titanite adopts space group A2/a implying that substitutions at the single octahedral site destroy the coherence of the off-centering of octahedral chains in the titanite structure resulting in a P2 1/a ? A2/a phase transition. Unit-cell dimensions obtained for the Al-Ta-Nb-rich titanite are: a = 7.0649(1) AÊ ; b = 8.7187(1) AÊ ; c = 6.5701(1) AÊ ; û = 113.755(1)ë, V = 370.41(1) AÊ 3. The extensive replacement of Ti by Al, Ta and Nb results in a considerable decrease in the distortion of all coordination polyhedra in the structure of this titanite. These structural data suggest that a solid solution CaTi 1ÿx(Alx/2 [Ta,Nb]x/2 )OSiO 4 (0 4 x 4 0.4) adopting the titanite structure might exist.
Keywords: titanite; Rietveld analysis; crystal structure; distortion; tantalum; niobium; aluminium